The Prevalence and Incidence of Dementia Due to Alzheimer's Disease: a Systematic Review and Meta-Analysis. (April 2016) - Fiest, Kirsten M.; Roberts, Jodie I.; Maxwell, Colleen J.; Hogan, David B.; Smith, Eric E.; Frolkis, Alexandra; Cohen, Adrienne; Kirk, Andrew; Pearson, Dawn; Pringsheim, Tamara; Venegas-Torres, Andres; Jetté, Nathalie
Abstract: Background: Updated information on the epidemiology of dementia due to Alzheimer's disease (AD) is needed to ensure that adequate resources are available to meet current and future healthcare needs. We conducted a systematic review and meta-analysis of the incidence and prevalence of AD. Methods: The MEDLINE and EMBASE databases were searched from 1985 to 2012, as well as the reference lists of selected articles. Included articles had to provide an original population-based estimate for the incidence and/or prevalence of AD. Two individuals independently performed abstract and full-text reviews, data extraction and quality assessments. Random-effects models were employed to generate pooled estimates stratified by age, sex, diagnostic criteria, location (i.e., continent) and time (i.e., when the study was done). Results: Of 16, 066 abstracts screened, 707 articles were selected for full-text review. A total of 119 studies met the inclusion criteria. In community settings, the overall point prevalence of dementia due to AD among individuals 60+ was 40.2 per 1000 persons (CI95% : 29.1-55.6), and pooled annual period prevalence was 30.4 per 1000 persons (CI95% : 15.6-59.1). In community settings, the overall pooled annual incidence proportion of dementia due to AD among individuals 60+ was 34.1 per 1000 persons (CI95% : 16.4-70.9), and the incidence rate was 15.8 per 1000 person-years (CI95% : 12.9-19.4). Estimates varied significantly with age, diagnostic criteria used and location (i.e., continent). Conclusions: The burden of AD dementia is substantial. Significant gaps in our understanding of its epidemiology were identified, even in a high-income country such as Canada. Future studies should assess the impact of using such newer clinical diagnostic criteria for AD dementia such as those of the National Institute on Aging–Alzheimer's Association and/or incorporate validated biomarkers to confirm the presence of Alzheimer pathology to produce more precise estimates of the global burden of AD. RÉSUMÉ: Prévalence et incidence de la démence due à la maladie d'Alzheimer : revue systématique et méta-analyse . Contexte: Nous avons besoin d'informations sur l'épidémiologie de la démence due à la maladie d'Alzheimer (MA) afin de nous assurer que des ressources adéquates sont disponibles pour satisfaire les besoins actuels et futurs de la population en soins de santé. Nous avons effectué une revue systématique et une méta-analyse de l'incidence et de la prévalence de la MA. Méthodologie: Nous avons effectué une recherche dans les bases de données MEDLINE et EMBASE de 1985 à 2012 ainsi que dans la liste de références d'articles retenus. Les articles retenus devaient fournir des estimations de l'incidence et/ou de la prévalence populationnelle de la MA. Deux évaluateurs ont revu indépendamment les résumés et le texte intégral ainsi que l'extraction des données des publications et en ont évalué la qualité. Nous avons utilisé des modèles à effets aléatoires pour générer des estimations regroupées stratifiées par âge, sexe, critères diagnostiques, lieu (continent) et temps (moment où l'étude a été réalisée). Résultats: Parmi les 16 066 résumés examinés, 707 articles ont été retenus pour une revue du texte intégral. En tout, 119 études rencontraient les critères d'inclusion. Dans la communauté, la prévalence ponctuelle globale de la démence due à la MA chez les individus de 60 ans et plus était de 40, 2 par 1 000 (IC à 95%: 29, 1 à 55, 6) et la prévalence annuelle pour les données regroupées était de 30, 4 par 1 000 (IC à 95%: 15, 6 à 59, 1). Dans la communauté, la proportion d'incidence annuelle globale regroupée de la démence due à la MA chez les individus de 60 ans et plus était de 34, 1 par 1 000 (IC à 95%: 16, 4 à 70, 9) et le taux d'incidence était de 15, 8 par 1 000 personnes-années (IC à 95%: 12, 9 à 19, 4). Les estimations variaient significativement selon l'âge, les critères diagnostiques utilisés et le lieu (continent). Conclusions: Le fardeau de la démence dû à la MA est considérable. Nous avons identifié des lacunes importantes dans notre compréhension de son épidémiologie, même dans un pays à revenu élevé comme le Canada. Des études ultérieures devraient évaluer l'impact de l'utilisation de critères diagnostiques plus récents pour identifier la démence due à la MA tels ceux du National Institute on Aging-Alzheimer's Association et/ou incorporer des biomarqueurs validés pour confirmer la présence de la pathologie de la MA et fournir des estimations plus précises de son fardeau global.